Analyzing the Role of an Online System in Reducing Learner’s Transactional Time in an Open and Distance e-Learning (ODeL) Environment: A Landscape Connectivity Perspective - Alip, Alvie Simonette Q.; Bagarinao, Ricardo T.; Secreto, Percia V.; Pamulaklakin, Rhodora L. (International Journal on Open and Distance e-Learning, 2020)
Geographical distance between the learners and the institution characterizes distance education (DE) mode of learning. Transactional time increases with distance. The rapid advances in Internet technology help reduce transactional time by allowing the development of online systems. Online systems such as the online request for document system, or ORDS helps facilitate students’ requests for and receipts of their academic records. However, there is a paucity of information on how such systems facilitate students’ requests and how students respond to the availability of such online systems. This information is vital in developing student support for DE learners because they are faced with multi-tasks, and time is an important element for their success. Using the landscape connectivity theory, this study was conceptualized to (a) evaluate whether ORDS reduces the transactional time of students in requesting and receiving documents, and (b) analyze students’ satisfaction level of using the system in terms of three usability criteria, namely, usefulness, ease of use, and efficiency. Data were collected through an online survey and retrieval of artifacts such as logbooks, emails, and reports. Results indicate that transactional time has been reduced from 12 days with a manual request system to 3.35 days with the online system. All criteria of usability received a satisfactory to very satisfactory evaluation from respondents with usefulness receiving the highest score among the three criteria. Results implied that online systems could enhance student connectivity with DE-providing institutions. Enhanced connectivity allows greater access to the institutions’ resources and services that could support students’ learning and persistence.